Increased shoulder distraction force and shoulder horizontal abduction in professional baseball pitchers with discordant torso rotation order - Manzi, J. E.; Dowling, B.; Dines, J. S.; Richardson, A.; McElheny, K. L.; Carr, J. B. (The American Journal of Sports Medicine, 2021)
Background: Inefficient energy transfer from the pelvis and trunk has been shown to increase compensation at the level of the shoulder. Kinetic chain sequencing of the core segments is underexamined in professional baseball pitchers, especially as it relates to changes in upper extremity kinetics.